2010
DOI: 10.4103/0973-1296.66931
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of hydro-alcoholic extracts of Cucurbita pepo and Solanum nigrum on HepG2 and CT26 cancer cell lines

Abstract: Plants are used worldwide for the treatment of diseases, and novel drugs continue to be developed through research from plants. There are more than 20,000 species of plants used in traditional medicines, and these are all potential reservoirs for new drugs. Cucurbita pepo has been used in traditional folk medicine to treat cold and alleviate ache. Previous pharmacological tests have shown that it possesses antiviral, anti-inflammatory, and analgesic effects. Also, Solanum nigrum has been used as a diuretic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 13 publications
0
33
0
1
Order By: Relevance
“…The ethanolic extract of fruits of C. pepo was observed to exhibit a significant dose-dependent inhibitory effect against HeLa cell growth [59].…”
Section: Anticancer/antitumour Effectsmentioning
confidence: 99%
“…The ethanolic extract of fruits of C. pepo was observed to exhibit a significant dose-dependent inhibitory effect against HeLa cell growth [59].…”
Section: Anticancer/antitumour Effectsmentioning
confidence: 99%
“…Plant extracts has molluscicidal activity against Galba truncatula (Hammami et al, 2011), in-vitro antiviral activity against Hepatitis C Virus (Javed et al, 2011) and used in the treatment of inflammatory bowel disease (Rahimi et al, 2010). Plant extract has potential application for treating metastatic melanoma (Wang et al, 2010), cytotoxic effect on HepG2 and CT26 cancer cell lines (Shokrzadeh et al, 2010) and in the treatment of breast cancer (Huang et al, 2010). Fruit extract of the plant has antioxidant and antihyperlipidemic activity (Arulmozhi et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Menéndez et al [10] remarked a significant decrease of the prostatic growth using a lipophilic extract of C. pepo seeds at doses of 400 and 200 mg/kg. Shokrzadeh et al [13] used hydroalcoholic extracts of C. pepo leaves on normal [Chinese hamster ovarian cells (CHO) and rat fibroblast] and cancer (HepG2 and CT26) cell lines with the following rank of inhibition ability: CHO < fibroblast < CT26 < HepG2 (being the lowest and the highest IC50 for HepG2: 132.6 µg/mL, and for fibroblast:293.2 µg/mL) cell lines. Other studies revealed that aerial parts of other Cucurbita species such as C. maxima also possess significant anticancer activity in Ehrlich ascites carcinoma model in mice which may be due to its cytotoxicity and antioxidant properties [4].…”
Section: Discussionmentioning
confidence: 99%
“…Shokrzadeh et al [13] reported different cytotoxic activities of the C. pepo leaf extracts on normal and cancer cell lines. Wang et al [14] observed a significant dose-dependent inhibitory effect against HeLa and HepG cell growth of the extract of C. pepo fruits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation